Does [Tf2N]− slither? Equivalence of cation and anion self-diffusion activation volumes in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide. Issue 23 (1st June 2022) - Harris, Kenneth R.; Kanakubo, Mitsuhiro
Abstract : High-pressure ion self-diffusion measurements for [EMIM][Tf2 N] show equivalent activation volumes: cation and anion transport processes are similarly affected by pressure. Abstract : New high-pressure self-diffusion data are reported for the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide ([EMIM][Tf2 N]) at pressures up to 363 MPa in the temperature range 288–348 K. The cation and anion activation volumes derived from these are found to be equal at a fixed temperature, within experimental error, in contradiction to a report in the literature that they differ significantly. Self-diffusion activation volumes derived from our earlier high-pressure diffusion studies also show equality for the respective cations and anions of bis(trifluoromethylsulfonyl)amide, tetrafluoroborate and hexafluorophosphate salts with various cations. Stokes–Einstein–Sutherland analysis and density scaling are applied to the [EMIM][Tf2 N] self-diffusion measurements and support the conclusion that pressure effects both cation and anion mass (and hence charge) transport in the same way. The density scaling parameters are consistent with the theoretical predictions of Knudsen et al. and agree with that for the viscosity, as for other ionic liquids.